The Arab Blogosphere and the Strategies of Self-Building and Diary - Ayyadhee, Nassir al-Deen (ALBAHITH ALALAMI, 2012)
Basically, media studies focused on the important role of the blogs in boosting the democratic process in the Arab States. Blogs also worked on creating an alternative media for the public that maintained freedom of expression. However, media studies ignored the status of the blogs in the social and cultural fields.The current study tries to tackle the socio-cultural dimensions of the blogs by means of showing how the blogs construct the self. The researcher is going to conduct interviews with the bloggers. He will also carry out a semiotic analysis that may reveal the strategies used by the bloggers. Besides, he tries to identify the realistic and traditional frames in which the social relationships are built and developed by means of these blogs